The protective effects of social bonding on behavioral and pituitary-adrenal axis reactivity to chronic mild stress in prairie voles. (4th March 2017) - McNeal, Neal; Appleton, Katherine M.; Johnson, Alan Kim; Scotti, Melissa-Ann L.; Wardwell, Joshua; Murphy, Rachel; Bishop, Christina; Knecht, Alison; Grippo, Angela J.
Abstract: Positive social interactions may protect against stress. This study investigated the beneficial effects of pairing with a social partner on behaviors and neuroendocrine function in response to chronic mild stress (CMS) in 13 prairie vole pairs. Following 5 days of social bonding, male and female prairie voles were exposed to 10 days of CMS (mild, unpredictable stressors of varying durations, for instance, strobe light, white noise, and damp bedding), housed with either the social partner (paired group) or individually (isolated group). Active and passive behavioral responses to the forced swim test (FST) and tail-suspension test (TST), and plasma concentrations of adrenocorticotropic hormone (ACTH) and corticosterone, were measured in all prairie voles following the CMS period. Both female and male prairie voles housed with a social partner displayed lower durations of passive behavioral responses (immobility, a maladaptive behavioral response) in the FST (mean ± SEM; females: 17.3 ± 5.4 s; males: 9.3 ± 4.6 s) and TST (females: 56.8 ± 16.4 s; males: 40.2 ± 11.3 s), versus both sexes housed individually (females, FST: 98.6 ± 12.9 s; females, TST: 155.1 ± 19.3 s; males, FST: 92.4 ± 14.1 s; males, TST: 158.9 ± 22.0 s). Female (but not male) prairie voles displayed attenuated plasma stress hormones when housed with a male partner (ACTH: 945 ± 24.7 pg/ml; corticosterone: 624 ± 139.5 ng/ml), versus females housed individually (ACTH: 1100 ± 23.2 pg/ml; corticosterone: 1064 ± 121.7 ng/ml). These results may inform understanding of the benefits of social interactions on stress resilience. Lay Summary: Social stress can lead to depression. The study of social bonding and stress using an animal model will inform understanding of the protective effects of social bonds. This study showed that social bonding in a rodent model can protect against behavioral responses to stress, and may also be protective against the elevation of stress hormones. This study provides evidence that bonding and social support are valuable for protecting against stress in humans.